Comparative study on the sedative effects of morphine, methadone, butorphanol or tramadol, in combination with acepromazine, in dogs - Monteiro, Eduardo Raposo; Rodrigues, Adolfo; Assis, Hemir Martins Quirilos; Campagnol, Daniela [UNESP]; Quitzan, Juliany Gomes [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
To compare the effects of morphine (MOR), methadone (MET), butorphanol (BUT) and tramadol (TRA), in combination with acepromazine, on sedation, cardiorespiratory variables, body temperature and incidence of emesis in dogs.Prospective randomized, blinded, experimental trial.Six adult mixed-breed male dogs weighing 12.0 +/- 4.3 kg.Dogs received intravenous administration (IV) of acepromazine (0.05 mg kg(-1)) and 15 minutes later, one of four opioids was randomly administered IV in a cross-over design, with at least 1-week intervals. Dogs then received MOR 0.5 mg kg(-1); MET 0.5 mg kg(-1); BUT 0.15 mg kg(-1); or TRA 2.0 mg kg(-1). Indirect systolic arterial pressure (SAP), heart rate (HR), respiratory rate (f(R)), rectal temperature, pedal withdrawal reflex and sedation were evaluated at regular intervals for 90 minutes.Acepromazine administration decreased SAP, HR and temperature and produced mild sedation. All opioids further decreased temperature and MOR, BUT and TRA were associated with further decreases in HR. Tramadol decreased SAP whereas BUT decreased f(R) compared with values before opioid administration. Retching was observed in five of six dogs and vomiting occurred in one dog in MOR, but not in any dog in the remaining treatments. Sedation scores were greater in MET followed by MOR and BUT. Tramadol was associated with minor changes in sedation produced by acepromazine alone.When used with acepromazine, MET appears to provide better sedation than MOR, BUT and TRA. If vomiting is to be avoided, MET, BUT and TRA may be better options than MOR.
Keywords: acepromazine; butorphanol; dog; methadone; morphine; tramadol